The Developing Pop Up Book Media to Teach Reading Narrative Text For Nine Grade At MTs Darun Najah Sambikarto - Risa Andriani; Mai Zuniati; Suhono, Suhono (CV. Creative Tugu Pena, 2024)
This study aims to develop a narrative text pop up book as a learning media and assess its feasibility for 9th-grade students at MTs Darun Najah Sambikarto. The research used Research and Development (RnD) Methodology, specificial the ADDIE model with stages including needs analysis, product development, product design, product implementation, and product evaluation. The fasibility of develop media is determined through expert validation in material and media. The study results indicate that the use of pop-up book media is valid for Mts Darun Najah Sambikarto students when reading narrative texts. This pop-up book proves to be beneficial in two key aspects: as a media tool (90%), and materials experts validation (92%). The satisfaction of students using this product is evident from the responses to a list of questions related to English language reading of narrative texts, with a high satisfaction rate of 86%.